2008
DOI: 10.1007/s00534-007-1319-1
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial use of the round ligament as a patch graft for vena cava reconstruction

Abstract: The use of an opened round ligament as a venous patch graft is an easy and feasible technique in patch reconstruction of the vena cava.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Hepatic round ligament (HRL), also called the ligamentum teres hepatis , is the remnant of the fetal umbilical vein and is connected to the falciform ligament. This ligament is well vascularized and extensible [ 16 ], and can therefore be harvested for enhancing venous- [ 17 ] or pancreatico-enterostomy[ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic round ligament (HRL), also called the ligamentum teres hepatis , is the remnant of the fetal umbilical vein and is connected to the falciform ligament. This ligament is well vascularized and extensible [ 16 ], and can therefore be harvested for enhancing venous- [ 17 ] or pancreatico-enterostomy[ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of various venous grafts used in HV reconstruction has been reported. These grafts include auto-venous grafts (from the inferior mesenteric vein, gonadal vein, external iliac vein, internal jugular vein, and saphenous vein)[ 13 , 15 , 16 ], venous grafts from a living donor, native portal veins[ 17 ], opened round ligaments[ 4 - 9 , 12 ], cryopreserved homografts[ 18 - 22 ], and polytetrafluoroethylene grafts[ 23 , 24 ]. However, the harvest of a venous graft from a living donor or the recipient himself is not easy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the opened round ligament as a venous patch graft has become accepted in hepatopancreatobiliary surgery because of its easy availability[ 1 - 3 ]. Recent studies have demonstrated the use of the opened round ligament as a venous patch graft in hepatic venous reconstruction during living donor liver transplantation (LDLT)[ 4 - 7 ]. However, there is no consensus regarding the efficacy of using the opened round ligament as a venous patch graft.…”
Section: Introductionmentioning
confidence: 99%
“…Although the case volume is limited, a higher incidence of thrombosis has been reported with the use of the opened round ligament as a long conduit . Yamanaka et al reported thrombosis in 2 of 6 patients who received cylindrically opened round ligaments for portal system reconstruction; these patients received grafts that were >3 cm long.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have proposed that the round ligament could be used as a venous patch graft in hepatobiliary surgeries . Nevertheless, there are several heterogeneous types of round ligaments, including unclosed umbilical veins procured during newborn delivery, spontaneously recanalized paraumbilical shunt vessels caused by liver cirrhosis, and manually opened and dilated round ligaments in adults . The opened round ligament, which is procured during laparotomy, could be procured from most donors and might be particularly useful for hepatobiliary surgeries, including LDLT .…”
mentioning
confidence: 99%